Portfolio considerations in differentiated product purchases: An application to the Japanese automobile market - Naoki Wakamori (Bank of Canada, 2011)
Consumers often purchase more than one differentiated product, assembling a portfolio, which might potentially affect substitution patterns of demand and, as a consequence, oligopolistic firms' pricing strategies. This paper studies such consumers' portfolio considerations by developing a structural model that allows for flexible complementarities/substitutabilities depending on consumer attributes and product characteristics. I estimate the model using Japanese household-level data on automobile purchasing decisions. My estimates suggest that complementarities arise when households purchase a combination of one small automobile and one minivan as their portfolio. Ignoring such effects leads to a overstated counterfactual analysis. Simulation results suggest that a policy proposal of repealing the current tax subsidies for small ecofriendly automobiles would decrease the demand for those automobiles by 9%; less than the 14% drop predicted by a standard single discrete choice model.
Keywords: D4; L5; Q5; 330; Economic models; Market structure and pricing